2021
DOI: 10.1186/s10195-021-00590-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival rates and reasons for revision of different stem designs in total hip arthroplasty for developmental dysplasia: a regional registry study

Abstract: Introduction Total hip arthroplasty (THA) in dysplastic hips is challenging, and each specific implant used in this context has been associated with specific complications. A registry study was performed to query survival rates, hazard ratios, and reasons for revision of different stem designs in THAs after developmental dysplasia of the hip. Materials and methods A regional arthroplasty registry was inquired about cementless THAs performed for hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…This study has some limitations due to the registry nature. Registries cannot provide those clinical and radiological outcomes that would be necessary to demonstrate the theoretical benefits of DT implants in terms of biomechanics restoration and improved implant stability [ 1 , 8 ]. Moreover, patient-reported outcomes were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has some limitations due to the registry nature. Registries cannot provide those clinical and radiological outcomes that would be necessary to demonstrate the theoretical benefits of DT implants in terms of biomechanics restoration and improved implant stability [ 1 , 8 ]. Moreover, patient-reported outcomes were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The regional arthroplasty registry RIPO provides active surveillance in the Italian region Emilia-Romagna (around 4,500,000 inhabitants), collecting data on hip, knee, and shoulder arthroplasties and revision surgeries since January 2000 [ 8 ]. Involving 68 orthopedic facilities in the region, the registry is a cross-checked database with a reported capture rate of 98%, with the 2% of missing data due to the lack of adherence [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martino et al [ 143 ] have reported the survival rates in an investigation of six different types of hip implants with different material combinations, wherein it was found that the CoC, CoP, and MoP material combination-type hip implants had a greater survival rate than the MoM-type hip implants did. Moreover, it is noticeable from in vitro, in vivo, and clinical studies that the fatigue life or survival of the hip implant is not only dependent on the mechanical properties of biomaterials.…”
Section: Biocompatibility and Tissue Response For Different Biomateri...mentioning
confidence: 99%
“…When hip dysplasia is present, nonmodular conical stem design increases the risk of cup aseptic loosening (2.5%) [55].…”
Section: Hip Dysplasiamentioning
confidence: 99%